2017
DOI: 10.1007/s10151-017-1666-0
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance defecography versus videodefecography in the study of obstructed defecation syndrome: Is videodefecography still the test of choice after 50 years?

Abstract: MR defecography could become the imaging test of choice for evaluating obstructed defecation syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
2
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 28 publications
0
20
2
2
Order By: Relevance
“…Furthermore, MRID appeared to underestimate the rectocele size, although it was able to detect a significant number of anatomical abnormalities missed on barium defecography in the anterior and middle pelvic floor compartments. Contrarily, however, higher MRID sensitivities for intussusception have been reported by the two most recent comparative studies . Nevertheless, pooled prevalence of the five comparative studies showed that barium defecography was superior to MRID in the detection of intussusception (57.8% vs 37.8%; OR: 1.52 [95% CI 1.12‐2.14, P = 0.009]), although the technique was associated with higher level of embarrassment (qualitatively measured among patients) and/or lower tolerance (54.3% vs 30.0%; OR: 1.73 [95% CI 1.14‐2.62, P = 0.008]) (Figure ).…”
Section: Summary Of Search Results and Study Qualitymentioning
confidence: 94%
See 3 more Smart Citations
“…Furthermore, MRID appeared to underestimate the rectocele size, although it was able to detect a significant number of anatomical abnormalities missed on barium defecography in the anterior and middle pelvic floor compartments. Contrarily, however, higher MRID sensitivities for intussusception have been reported by the two most recent comparative studies . Nevertheless, pooled prevalence of the five comparative studies showed that barium defecography was superior to MRID in the detection of intussusception (57.8% vs 37.8%; OR: 1.52 [95% CI 1.12‐2.14, P = 0.009]), although the technique was associated with higher level of embarrassment (qualitatively measured among patients) and/or lower tolerance (54.3% vs 30.0%; OR: 1.73 [95% CI 1.14‐2.62, P = 0.008]) (Figure ).…”
Section: Summary Of Search Results and Study Qualitymentioning
confidence: 94%
“…Rectocele has traditionally been defined as an outpouching of the rectal wall on defecation . A total of 17/41 studies defined a cut‐off of rectocele depth to establish the diagnosis: 2 cm (n = 9); 2.5 cm (n = 1); 3 cm (n = 4); or 4 cm (n = 3) . However, the approach adopted to calculate rectocele size during maximum straining has been detailed in only nine of these as: (a) the “maximum depth of the bulge beyond the expected and extrapolated line of the anterior rectal wall” (n = 2); the “distance between the maximal anterior outbulge” and (b) the “axis of the anal canal” (n = 2), or (c) “a line through aspect of anorectal junction” (n = 1), or “a line drawn parallel to the center of the anal canal during straining” (n = 2); d) “outpouching of the anterior rectal wall ahead of rectovaginal septum, persisting on incomplete evacuation” (n = 2) …”
Section: Summary Of Search Results and Study Qualitymentioning
confidence: 99%
See 2 more Smart Citations
“…Por su parte, Laura Solé presenta en el tercer artículo una revisión muy completa de la literatura de los últimos 10 años sobre los trastornos de la evacuación 11 . Si bien dichos trastornos se clasifican mediante los criterios de Roma IV 12 , requieren el uso de pruebas fisiológicas como manometría anorrectal, prueba de expulsión del balón y estudios de imagenología como defecografía convencional y por resonancia magnética (RM) [12][13][14] . Desde el punto de vista de los estudios de imagen, habrá que determinar si la defecografía por RM podrá reemplazar a la convencional, puesto que parece ser superior en la detección de enteroceles, pero presenta menor tasa de detección para rectoceles, intususcepción y descenso perineal 14 .…”
unclassified